Tecitura poeticopedagógica: a palavra como presença no processo de criaçao em dança - Colognese, Milena (2017)
This dissertation proposes to describe the construction of a pedagogy of the creative process in dance from the relation between the danced movement and word. The research has a qualitative approach with a narrative type, and it starts from the narratives of the creation process to extract problems and move concepts. The reports of the practical experiments made while the researcher wrote this text highlight some recurrent elements of the relation between the poetic word and the dance movement: literality, non-action and memory. In order to present the ways in which the researcher engenders knowledge through the process of creation, the objective is to develop a reflection about the relationship between the word and danced movement, and to describe the implicit pedagogies of the creation process. The writing is about the poetic use of the word - reading poems, for example - and the resulting movement - gesture, voice, danced movements. In the contact with the materialities, it is intuited that the link of the word with the movement occurs in the production of presence and as a performative action, that is, the word as presentification of the senses produced in reading, as event, occurrence, performance. The relevance of the study revolves around the emergence and rescue of the poetic word in artistic and pedagogical practices. New forms of teaching/learning are indicated in the scope of Dance and literary reading, in which the poetic use as a potent producer of culture is perceived. The research, inserted in the field of Education and Art, reveals itself as a search for the legitimation and relation of knowledge through the process of creation in dance, whose experience presents itself, therefore, as poetic-pedagogical.